Collaborative Decision for Building Energy System on Traditional Markets in Urban Areas - Christiono Utomo; Yani Rahmawati; Nugroho Priyo Negoro (Institut Teknologi Sepuluh Nopember, 2017)
It becomes more important to design energy-efficient for buildings. This is true in relationship to a public building design especially retail property such as traditional market. It calculates the use of energy during construction and operation. There are three alternatives for a building energy system which are passive energy, electrical equipment, and user processes. The alternatives are developed for a public commercial retail. They were selected by four stakeholders named government, tenant, designer, and property manager. It is not easy to make a decision where there are many stakeholders' interests. A decision support system is necessary. The system should support a collaborative process among decision makers. This paper presents a multi criteria and multi person decision process to develop agreement options and coalition formation to find the best fit option of the energy system for traditional markets building in urban areas. There are three stages involved in the process which are first is determining and scoring of every alternative for every stakeholder, second is determining the optimal solution (payoff optimum) for each stakeholder in a coalition, and third is analyzing the best fit options for every coalition and grand coalition. An analytical hierarchy process (AHP) based on satisfying option is applied for the first stage. A liner programming is used to determine payoff optimum in the stage two and an agent system based on game theory built the coalition algorithm on the stage three. The result shows a model of collaborative decision to select a building system at design process.